The Happy Worker: Revisiting the “Happy-Productive” Worker Thesis - Hosie, Peter; ElRakhawy, N. (Wiley-Blackwell, 2014)
Part of the six-volume reference set Wellbeing: A Complete Reference Guide, this volume is a comprehensive look at wellbeing in the workplace at organizational, managerial, and individual levels.